Marvel "Tsum Tsum" takeover! - Chabot, Jacob (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2017)
"Marvel super heroes plus a world-conquering toy craze... In case you've been living under a rock, Tsum Tsum are huge! Well, not literally--they're actually pretty tiny--but these cute-and-cuddly creatures are sweeping the globe! So what happens when these pint-size piles of fur find their way into the Marvel Universe? When a crate of Tsum Tsum falls to Earth en route to the Collector, a group of Brooklyn teenagers will find out! Will the little critters make it out in one adorable piece--and can the kids survive an attack from Ultron?--Back cover.